INTERPRETATION AND MANIFESTATION OF VALUES OF SUNDAN PHILOSOPHY "CAGEUR, BAGEUR, SINGER" - Riska Novianty; Yusuf Tri Herlambang (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Background: The philosophy of "Cageur, Bageur, Singer" represents Sundanese local wisdom containing character education values and personality formation. In the context of modernization, these values need systematic examination to understand their relevance to national character development. Objective: This study aims to analyze the interpretation and manifestation of Sundanese philosophical values "Cageur, Bageur, Singer" through a systematic literature review. Methods: This research employs Systematic Literature Review (SLR) methodology with PRISMA protocol. Literature search was conducted in Scopus, Google Scholar, and Portal Garuda databases for the period 2014-2024 using keywords "Cageur Bageur Singer", "Sunda philosophy", "local wisdom", and "character education". From 247 identified articles, 58 articles met inclusion criteria and were thematically analyzed. Results: Analysis reveals three main dimensions: (1) "Cageur" is interpreted as physical, mental, and spiritual health manifested in healthy lifestyle patterns and psychological resilience; (2) "Bageur" reflects moral goodness manifested in prosocial behavior, empathy, and social ethics; (3) "Singer" depicts holistic intelligence manifested in intellectual competence, practical skills, and wisdom. Implementation of these values is found in educational practices, organizations, and contemporary Sundanese community life. Conclusion: The philosophy of "Cageur, Bageur, Singer" has contemporary relevance as an integrative character education framework, combining health, morality, and intellectuality dimensions in holistic human development.